Sub-regional integration and democratisation in Africa : critically analysing the approach of the ECOWAS in West Africa - Benner, Yaw (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.